The power of competence support: The impact of coaches and athlete leaders on intrinsic motivation and performance - Fransen, K.; Boen, F.; Vansteenkiste, M.; Mertens, N.; Vande Broek, G. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Grounded in the Cognitive Evaluation Theory, a mini-theory of Self-Determination Theory, this experimental field study sought to examine the impact of competence support of both coaches and athlete leaders on athletes` competence satisfaction, intrinsic motivation, and subjective as well as objective performance. Male basketball players (N = 120) were allocated to groups of 5 players. These groups were then randomly assigned to a control group or to 1 of 3 experimental conditions. In these experimental conditions, either the coach, the athlete leader, or both provided motivational feedback to their team. The provision of motivational feedback by either the coach or the athlete leader was sufficient to increase athletes` competence satisfaction, intrinsic motivation, and objective performance (i.e., enhanced execution time without a decrease in scoring percentage) relative to the control group. Interestingly, when both the coach and the athlete leader provided competence support, a surplus effect was observed on objective performance compared with when only the coach provided competence support. Furthermore, structural equation modeling revealed that players` competence satisfaction mediated the relationship between the provided competence support and players` intrinsic motivation, while a direct effect was observed on objective performance. In conclusion, the study findings indicate that also athlete leaders can adopt a motivating role, and that by doing so, their impact is as strong as the impact of the coach. Both coaches and athlete leaders can thus boost athletes` objective performance and foster competence satisfaction, with the latter resulting in increased intrinsic motivation.